COMPARATIVE EVALUATION OF SRTM, ASTER, AIRBUS, AND ALOS DEMS FOR HYDROLOGICAL RESEARCH ACROSS DIVERSE TERRAIN TYPES (ҚазҰУ Хабаршысы. География сериясы, 2025)
Digital Elevation Models (DEMs) are a key tool for hydrological modeling and water resource analysis, enabling more accurate assessment of runoff processes, precipitation distribution, and flood risks. This study presents a comparative analysis of four global DEMs: Airbus WorldDEM4Ortho, ALOS AW3D, SRTM, and ASTER GDEM, aimed at evaluating their accuracy and practical applicability across different landscape conditions, including mountainous and flat terrains. To assess model quality, state geodetic points with high-precision elevation control and topographic maps were used, providing a reliable reference for comparison. Additionally, river networks extracted from the DEMs were compared with reference data obtained from Landsat 8 and Sentinel 2 satellite imagery, allowing verification of hydrological representation accuracy.The results indicate that Airbus WorldDEM4Ortho demonstrates the highest vertical accuracy and offers a more detailed and accurate representation of river networks due to its high spatial resolution and quality source data. The ALOS AW3D model showed comparable accuracy and hydrological reproduction, making it a worthy alternative. Meanwhile, the SRTM and ASTER GDEM models exhibit noticeable deviations, especially in flat areas, reducing their suitability for detailed hydrological modeling. Nevertheless, SRTM remains widely used due to its free accessibility, stability, and sufficient accuracy for large-area analyses. In contrast, ASTER GDEM is less suitable for high-resolution and detailed hydrological analysis tasks.This study emphasizes the critical importance of selecting the appropriate DEM based on terrain type and specific hydrological analysis goals, as this significantly impacts the quality of risk assessment related to water resource management and engineering planning